T.S. Eliot and the art of collaboration - Badenhausen, Richard (Cambridge University Press, 2004)
"Richard Badenhausen examines the crucial role that collaboration with other writer's played in the development of T.S. Eliot's works from the earliest poetry and unpublished prose to the late plays.